2021
DOI: 10.3892/or.2021.8245
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI‑based radiomics in locally advanced rectal cancer (Review)

Abstract: Colorectal cancer is the third most common type of cancer, with high morbidity and mortality rates. In particular, locally advanced rectal cancer (LARC) is difficult to treat and has a high recurrence rate. Neoadjuvant chemoradiotherapy (NCRT) is one of the standard treatment programs of LARC. If the response to treatment and prognosis in patients with LARC can be predicted, it will guide clinical decision-making. Radiomics is characterized by the extraction of high-dimensional quantitative features from medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…In addition, as studies on radionomic analysis to improve the prediction of pCR have recently been reported, further imaging methods may help select high-risk patients. 20 21 22 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, as studies on radionomic analysis to improve the prediction of pCR have recently been reported, further imaging methods may help select high-risk patients. 20 21 22 …”
Section: Discussionmentioning
confidence: 99%
“…Those features are mathematical descriptions of the visual properties of an image [20][21][22]. For instance, numerical values are included, such as actual pixel intensities, edge strengths, shape descriptors, and regional variation or texture of pixel value [23], which can provide accurate and reliable evidence to aid in clinical decision-making [24,25]. For instance, a review study conducted by Lohmann et al illustrated the relationship between imaging features and clinicopathological manifestations of gliomas, in which the value of the features in diagnosing gliomas was demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Once radiomics will be included in the clinical practice, it could help in improving the management of patients with LARC, providing tailored treatments, avoiding unnecessary toxicity to patient predicted unlikely to respond, and consequently anticipating the radical treatment or switching to an intensified treatment when necessary. Recent studies have explored the potential to predict long-term survival of patients with LARC [11], to discriminate different stages of rectal cancer [12], and to predict response to neoadjuvant chemoradiotherapy to identify patients eligible for less invasive treatments [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%